Activation of mitochondrial aldehyde dehydrogenase (ALDH2) by ALDA-1 reduces both the acquisition and maintenance of ethanol intake in rats: A dual mechanism?. (1st March 2019) - Rivera-Meza, Mario; Vásquez, David; Quintanilla, María Elena; Lagos, Diego; Rojas, Braulio; Herrera-Marschitz, Mario; Israel, Yedy
Abstract: A number of pre-clinical studies have shown that brain-generated acetaldehyde, the first metabolite of ethanol, exerts reinforcing effects that promote the acquisition of ethanol intake, while chronic intake maintenance appears to be mediated by alcohol-induced brain neuroinflammation/oxidative stress. Recently, it was described that N-(1, 3-benzodioxol-5-ylmethyl)-2, 6-dichlorobenzamide (ALDA-1) activates aldehyde dehydrogenase-2 (ALDH2), enzyme that catalyzes the oxidation of ethanol-derived acetaldehyde to acetate. The aim of this study was to determine the effects of ALDA-1 on both the acquisition and the maintenance of alcohol intake in alcohol-preferring UChB rats. For ethanol acquisition studies, naïve UChB rats were treated with five daily doses of ALDA-1 (12.5, 25 or 50 mg/kg, i.p.) from one day before the start of ethanol exposure. For chronic intake studies, UChB rats exposed for 98 days to a free access to 10% ethanol and water were treated daily with ALDA-1 (12.5, 25 or 50 mg/kg, i.p.) for five days. The administration of ALDA-1 reduced by 72–90% ( p < 0.001) the acquisition of ethanol consumption in naïve rats. At chronic ethanol consumption, ALDA-1 reduced ethanol intake by 61–82% ( p < 0.001). ALDA-1 administration increased by 3- and 2.3-fold the activity of ALDH2 in brain and liver, respectively. ALDA-1 did not affect saccharin consumption, nor it modified the rate of ethanol elimination. The study shows that the activation of ALDH2 by ALDA-1 is effective for inhibiting both the acquisition and the maintenance of chronic ethanol intake by alcohol-preferring rats. Thus, the activation of brain ALDH2 may constitute a novel approach in the treatment of alcohol use disorders. Highlights: ALDA-1 increased by 3-fold the brain ALDH2 activity in rats. ALDA-1 blocked the acquisition of ethanol intake. ALDA-1 reduced by 61–82% chronic ethanol intake. ALDA-1 did not modify voluntary saccharin consumption. ALDA-1 did not change the rate of ethanol elimination.